Otomasi Kamera Perangkap Menggunakan Deteksi Gerak dan Komputer Papan Tunggal - Habib Dwi Cahya; Agus Harjoko (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2019)
USB camera is currently used in daily life for various purposes. On its development, the use of USB camera can be used to create camara traps and can be used to observe the development of animal with integrated systems. In this research, motion detection was used to observe animals online using Single Board Computer (SBC) Camera trap in this research using Single Board camera in form of raspberry pi 3 B. Python proggramming language is used with OpenCV library. The method used to detect motion is the Mixture of Gaussian (MOG). The result image gained by motion detection will be uploaded to the dropbox API.The test performed on 11 videos, the system can process images with 320x240 resolution. The test results show the best blut value of k = 13, the best threshold value is 100 pixel with an accuracy of 80,3%, and the maximum distance system can detect animal objects as far as 6m. The response time gained for the sytem to process frame per second have average of 0,098 seconds, while for uploading image to dropbox han an average of 1,618 seconds. The test result show the system still has room for development and improvement.